Policing serious fraud in New Zealand - Newbold, Greg (Crime, law and social change, 1993)
The discovery of a serious fraud problem in New Zealand is very recent. Prior to the 1980s, there had been only three prosecutions for serious fraud in the history of the country, and penalties for those convicted were small. But a corporate boom in the 1980s, followed by the sharemarket crash of 1987, revealed extensive serious fraud. Initial attempts to combat the problem through the Commercial Affairs division of the Department of Justice failed. But in 1990 a Serious Fraud Office was established, with powers greater than those ever given before to a New Zealand law-enforcement agency. Three years later, the SFO had been notified of possible frauds totalling $ 2.5 billion. This represents many times what is reported stolen in all other property crime, but the SFO budget is only 1% of that devoted to ordinary policing. Since 1990, only one prosecution out of the seventeen completed has failed. Prison sentences of up to seven years and averaging almost four years, have been awarded. As the SFO nears the end of its third year, and its net gradually widens, its influence on illegal business activity continues to grow.